PERENCANAAN STRATEGIS SISTEM INFORMASI DESA DAN KAWASAN PERDESAAN MENGGUNAKAN KERANGKA KERJA TOGAF ADM - Suarezsaga, Fredrikus; Wisnubadhra, Irya; Purnomo W.P, Y. Sigit (Proceeding SENDI_U, 2015)
The Indonesia Government on period 2014-2019, endorsed 2014-2019âs Rencana Pengembangan JangkaMenengah Nasional (RPJMN) with concept of developing Indonesia from the edge. One focus of RPJMN isreduction of inequality interregion and itâs to be strengthened with the UU Desa and supported PP No. 43 year2014 concerning implementing the law No. 6 year 2014 concerning the village and PP no. 60 of 2014 on DanaDesa sourced from APBN. The database about the villages have been formulated in the Pedoman PenyusunanPendayagunaan Data Profil Desa dan Kelurahan through Permendagri No. 12 year 2007 in the form softwareand information system (IS) called Profil Desa dan Kelurahan. Implementation of the village profile and has notyet optimal, existing data cannot be integrated with the other villages, and the other data for villages authorities.IS that has been developed is still limited functionality in demographic data services. This paper will be to planand design a strategic planning for information systems that will be developed using the Enterprise Architectureof TOGAF ADM framework. Strategic planning aligned with the village authorities in the UU Desa No. 6 year2014. The result shows the implementation in the tasks and authority and decision making.Keywords: UU Desa No.6 Tahun 2014, strategic planning, information system